2013
DOI: 10.17221/352/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fibre addition on the rheological and sensory properties of dough and bakery products

Abstract: Wheat, apple, potato, and bamboo fibres were applied at 1 and 3% content to bread wheat flour and these additions were studied for the quality of dough and bakery products characterised by farinograph parameters, laboratory baking tests, firmness, and sensory analysis. The addition of fibre caused a decrease of loaf volume, also a change of crumb colour and a slight increase of bread crumb firmness. On the other hand, the addition of fibre affected the farinograph parameters, significantly decreased the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…In the present study, DOF was incorporated at higher amount than in previous studies (42,43) and experimental brioches showed higher content of protein, and lower percentage of ash (at 30 and 50% of fat replacement) in discordance to findings reported by Nassar et al (40).…”
Section: Discussioncontrasting
confidence: 73%
“…In the present study, DOF was incorporated at higher amount than in previous studies (42,43) and experimental brioches showed higher content of protein, and lower percentage of ash (at 30 and 50% of fat replacement) in discordance to findings reported by Nassar et al (40).…”
Section: Discussioncontrasting
confidence: 73%
“…However, this effect could be also related to some sort of competition for water between fibre and the other flour components, which leads to a progressive dehydration of dough creating the impression of dough strengthening (Gómez et al, 2011). The same effect on DDT was observed by Kučerová et al (2013), Borchani et al 2011and Mohammed et al (2012), who substituted wheat flour by potato fibre, date flesh and chickpea flour, respectively. Dough stability (DS) indicates how much tolerance the flour has to over-or under-mixing (Bakare et al, 2015).…”
Section: Resultsmentioning
confidence: 83%
“…Bread contains a plethora of important nutritional components which exert a positive influence on the human health. In spite of this, the addition of fibre into bread and wheat products is still very important (Kučerová et al, 2013). Peels are the major by-product of potato processing industries and contain the same amount of valuable compounds as edible vegetable (Mirabela et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The SDS is converted into glucose when digested in the small intestine for up to 120 min . The RS passes into the colon, where it is metabolized into secondary products (short chain fatty acids) by colonic microflora and behaves in a way similar to dietary fiber . Resistant starch is classified into several categories.…”
Section: Introductionmentioning
confidence: 99%